Caring With Compassion, Domain 2: Bio-Psychosocial Care of Uninsured, Homeless, Underserved, and At-Risk Populations - Davoren Chick; April Bigelow; Frank Jacob Seagull; Heather Rye; Pamela Davis; Brent Williams (Association of American Medical Colleges, 2014)
Abstract Introduction The Caring with Compassion series provides core background information to support bio-psychosocial clinical care for homeless, underserved, uninsured, and at-risk populations. At the University of Michigan Medical School, this content serves as a core resource for a fourth-year medical student clinical elective regarding care of the underserved. At the University of Michigan School of Nursing, it is a core resource for advance nurse practitioner clinical rotations in underserved settings. For graduate medical learners, the content is available as an independent learning resource. This resource is the second domain in a two-domain series. The first domain provides an overview of US public health care systems, while this domain presents the bio-psychosocial model of health care and special care needs of underserved populations. Methods In this module, case-based materials are provided to address the topics of biomedical conditions among the homeless, social determinants of health, the biopsychosocial model of health, and interdisciplinary team care. A multiple-choice test and answer key are provided for each topic. Results Nationally, over 300 learners from multiple medical and nursing training programs have registered as learners, and feedback has been highly positive. Through the use of t tests, preliminary quantitative outcome data demonstrated significant improvement in multiple-choice examination scores following exposure to the modules for all assessed content areas: epidemiology of populations in need (n = 42, pretest = 49%, posttest = 81%, p < .0001); health care delivery systems knowledge (n = 19, pretest = 53%, posttest = 67%, p < .002); homelessness and disease (n = 20, pretest = 59%, posttest = 82%, p < .0001); public health insurance (n = 30, pretest = 52%, posttest = 80%, p < .0001); team care (n = 14, pretest = 45%, posttest = 64%, p < .001); social determinants (n = 29, pretest = 51%, posttest = 56%, p = .022). Additionally, comments from users included: "This is incredible and I am going through it slowly - realize how much I need to learn," "A great tool for everyone not only to raise awareness but hopefully inspire people to take an active role in the care of the underserved." Discussion Most training programs find it easiest to utilize this resource then encourage application in clinical settings. For programs with residents providing continuity care in federally qualified health care centers, the content may be used for ambulatory case conference discussions.